Endoscopy in Obesity Management A Comprehensive Guide (Springer International Publishing, 2018)
This text will provide a comprehensive, state-of-the art review of endoscopy in the management of the obese patient. It will serve as a valuable resource for clinicians, surgeons, endoscopists and researchers with an interest in endoscopy in the role of obesity care. The book will review how endoscopy plays a crucial role in the preoperative evaluation of a patient undergoing a surgical or endoluminal intervention, how intra-operative endoscopy allows evaluation of the newly reconstructed gastrointestinal tract and how post bariatric surgery complications can be managed. Endoscopic evaluation of normal and abnormal surgical anatomy will also be covered. A section dedicated to current and future endoluminal therapies, with a focus on safety, efficacy and technique, will also be thoroughly reviewed. This text will serve as a very useful resource for endoscopy in both a surgical and gastroenterology practice. Training, credentialing and the implementation of EBTs into ones practice, endoscopy suite and hospital will also be discussed.